SMARTPLS APPROACH IN INVESTIGATING THE DETERMINANTS OF UNEMPLOYMENT CRISIS AMONG GEN Y - Nor Azilah Husin; Amirul Syafiq Mohd Ghazali; Salina Rasli (International Journal of Accounting, Finance and Business, 2021)
Employment Insurance Security reported that the unemployment in Malaysia keeps on increasing. The situation is more worrying as the pandemic of Covid-19 resulted in many businesses stopping operating either temporarily or permanently. The fresh new graduates, who lack experience, find it extra challenging to seek employment. This study aims to explore the determinants of the unemployment crisis among Gen Y. The data were analyzed using the Partial Least Square (PLS) to predict the unemployment crisis factors. The findings revealed that R Square 57.7% of the total variation in unemployment is explained by attributes and economic uncertainty. Employers' preference does not impact the unemployment crisis. The results should shed light on the related stakeholders, e.g., unemployed graduates, to prepare themselves for suitable employment, and the company needs to relook on the current situation.